Facile synthesis of novel CoWO4/FeWO4 hetrocomposite with efficient visible light photocatalytic degradation and hydrogen evolution aspects - Muhammad Munir Sajid; Thamer Alomayri; Haifa Zhai (Journal of Taibah University for Science, 2023)
ABSTRACTTungstate-based nanomaterials exhibit efficient photocatalytic performance and offer several advantages owing to their electrical and superior optical features, charge transport potentials, and superb corrosion resistance. The objective of the present study is to fabricate cobalt tungstate (CoWO4), Ferric tungstate (FeWO4) and CoWO4/FeWO4 heterojunction composite photocatalysts using a hydrothermal route with various molar concentrations (2:1, 1:1, 1:2, 1:5). The model pollutant Methyl Orange (MO) and Congo Red (CR) azo dyes were degraded 98.26% and 99.61% in 150 min by the as-synthesized CoWO4/FeWO4 at a molar concentration ratio of 1:2. A feasible photodegradation mechanism is purposed and the optimum values for different parameters are also evaluated by considering two different dyes as model organic pollutants. Hydrogen production efficiency reaches up to 36 μmolg−1 h−1 under visible light over 1:2 CoWO4/FeWO4. This work may open new possibilities for the use of CoWO4/FeWO4 composite for potential applications such as the hydrothermal synthesis of composites and their photocatalytic wastewater remedy and as hydrogen evolution applications.